2016
DOI: 10.2134/agronj2016.03.0128
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Strategy and Seeding Rate Affect Rice Lodging, Yield, and Economic Returns in the Midsouthern United States

Abstract: core ideas• Split N application in rice limits lodging but also reduce grain yield.• High N rates and seeding rates increase lodging and harvest costs.• Appropriate early-season (prefl ood) N is necessary to maximize rice grain yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…When averaged across TE rates and timings 100% of N applied at V3 resulted in 4% (12,083 vs. 11,542 kg ha -1 ) greater grain yield than the split application strategy. Multiple studies evaluating modern rice cultivars have reported increased grain yield when all N fertilizer is applied preflood compared to split applications (Bollich et al, 1994, Norman et al, 2000Slaton et al, 2003;Bond et al, 2008;Corbin et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…When averaged across TE rates and timings 100% of N applied at V3 resulted in 4% (12,083 vs. 11,542 kg ha -1 ) greater grain yield than the split application strategy. Multiple studies evaluating modern rice cultivars have reported increased grain yield when all N fertilizer is applied preflood compared to split applications (Bollich et al, 1994, Norman et al, 2000Slaton et al, 2003;Bond et al, 2008;Corbin et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…NRI and NBI at the late filling stage can thus be used to better predict grain yield. However, rice yield could change as a result of the interaction of complex factors [29, 30], such as unusual precipitation and temperature, which can cause rice lodging and disease [3133]. Therefore, actual rice yield may differ from the yield predicted by NRI and NBI at the late filling stage, so these predictions should be used cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, N application at panicle initiation stage of rice increases grain yield by increasing grain weight in inferior spikelets (19). However, application of N at late vegetative stage delays maturity and increases chances of lodging (20). Therefore, field optimisation of rate and exact time of N application must to studied for economic yield returns along with quality grains.…”
Section: Discussionmentioning
confidence: 99%